DINAMIKA USAHA MASYARAKAT NELAYAN DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA DI KAMPUNG SARAWANDORI DISTRIK KOSIWO KABUPATEN KEPULAUAN YAPEN PROVINSI PAPUA - Mamoribo, Martince; PARTINI, PARTINI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesia is islands nation, consist of about 17.504 islands with the coastal line length about + 51.000 km, and within this coastal line there are coastal area that narrow relatively but rich of natural resource potensial. But until to now, the fishermans these marine potencies still not be utilized yet. Even most of these fishermans still live under the poverty line with per capita income less than 10 US dollar each month (Hendratmoko and Marsudi, 2010). Including this was the fishermans in Sarawandori Village, Kosiwo District, Yapen Islands Regency. Various effort had been performed by the regional government to deveoping the fishermans community, but not showed yet the encourage result. Thus, it was needed to perform a study on âThe business dynamics of fisherman community to increasing their family welfare in Sarawandori Village, Kosiwo District, Yapen Islands Regency, Papua Provinceâ. The study was aimed to knowing how the business dynamics of the fisherman and how their welfare level in Sarawandori Village, Kosiwo District, to increasing their family welfare. This is qualitative descriptive study, was performed in Sarawandori Village, Kosiwo District, Yapen Islands Regency, Papua Province. The study involved 25 informants to explore an information that needed by the study. The result of the study showed that the catch fishery business by the fishermans community in Sarawandori Village was less dynamics, as characterized by: a). The tehcnology that was used still traditional